HELPER study: A phase II trial of continuous infusion of endostar combined with concurrent etoposide plus cisplatin and radiotherapy for treatment of unresectable stage III non-small-cell lung cancer. (February 2019) - Zhai, Yirui; Ma, Honglian; Hui, Zhouguang; Zhao, Lujun; Li, Dongming; Liang, Jun; Wang, Xiaozhen; Xu, Liming; Chen, Bo; Tang, Yu; Wu, Runye; Xu, Yujin; et al.
Highlights: This prospective study sought to evaluate the efficacy and toxicities of the addition of endostar, an anti-angiogenesis agent, to concurrent etoposide, cisplatin (EP) and radiotherapy for treatment of patients with stage III NSCLC. The median times of PFS and OS were 13.3 months and 34.7 months and toxicities were tolerable. Abstract: Purpose: The prognosis of unresectable stage III non-small cell lung cancer (NSCLC) was poor even after concurrent chemoradiotherapy. There remains a great need to develop novel therapeutic agents in combination with CCRT to improve outcomes. This prospective study sought to evaluate the efficacy and toxicities of the addition of endostar, an anti-angiogenesis agent, to concurrent etoposide, cisplatin (EP) and radiotherapy for treatment of patients with NSCLC. Patients and methods: Patients with untreated pathologically confirmed inoperable stage III NSCLC were eligible. Radiation at doses of 60–66 Gy, four cycles of endostar (7.5 mg/m 2 /24 h × 120 h, 14 days/cycle), and two cycles of EP (etoposide 50 mg/m 2 on days 1–5 and cisplatin 50 mg/m 2 on days 1 and 8, 28 days/cycle) were delivered. The primary endpoint was progression-free survival (PFS). The secondary endpoints were response rate and overall survival (OS), locoregional relapse-free survival (LRFS) distant metastasis-free survival (DMFS) and adverse events (AE). Results: From November 2012 to June 2015, 73 patients were enrolled, and 67 patients were evaluable. The median age was 59 years. Sixty-six percent of the patients had squamous cell carcinoma. Grade ≥3 AEs occurred in 58.2% of the patients. The most common Grade ≥3 AE was leucopenia (44.8%). The response rate was 76.1%. The median times of PFS and OS were 13.3 months and 34.7 months, respectively. The 2-year PFS, OS, LRFS and DMFS rates were 34.8%, 59.9%, 54.7% and 68.5%, respectively. Conclusions: For patients with unresectable stage III NSCLC, continuous intravenous endostar in combination with concurrent EP and radiotherapy did not prolong median PFS, although it got preferable OS, promising 2-year PFS with tolerable toxicities.